2021
DOI: 10.1016/j.str.2021.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of hydrogen atoms in a perdeuterated lectin-fucose complex reveals key details of protein-carbohydrate interactions

Abstract: Highlights d Joint X-ray/neutron structure of bacterial lectin in apo and complex form d Perdeuterated lectin and sugar improve the quality of neutron density maps d Fucose methine and methyl groups are involved in CH-p interactions with tryptophan d Room temperature data avoid glycerol-induced alternate loop conformations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…A high-resolution crystal structure of LecB has been obtained previously 14 , but the role of the two calcium ions in the high-affinity binding of fucose remains unclear and further structural analyses are required. Neutron macromolecular crystallography is the technique of choice for determining the positions of hydrogen atoms and the protonation states of active groups 18 21 that are involved in the catalytic activity of enzymes or the binding of a ligand to a macromolecule 22 25 . Moreover, neutrons do not cause any radiation damage to the biological sample so the structure determination and data collection can be performed at room temperature (RT), giving a more accurate view of local flexibility and water mobility at biologically relevant temperatures 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…A high-resolution crystal structure of LecB has been obtained previously 14 , but the role of the two calcium ions in the high-affinity binding of fucose remains unclear and further structural analyses are required. Neutron macromolecular crystallography is the technique of choice for determining the positions of hydrogen atoms and the protonation states of active groups 18 21 that are involved in the catalytic activity of enzymes or the binding of a ligand to a macromolecule 22 25 . Moreover, neutrons do not cause any radiation damage to the biological sample so the structure determination and data collection can be performed at room temperature (RT), giving a more accurate view of local flexibility and water mobility at biologically relevant temperatures 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Studying the effect of glycerol at the atomic level requires structural data of the highest quality, which are rarely available. Recently, Gajdos and coworkers reported that glycerol causes alternative loop conformations between repeats in the structure of the lectin PLL from Photorhabdus laumondii (Gajdos et al, 2021). Another notable example is human carbonic anhydrase II.…”
Section: Discussionmentioning
confidence: 99%
“…I am grateful to the University of Manchester Department of Chemistry for continued support. As a further measure of the growth and importance of the theme of neutron protein crystallography in general and its use to determine lectin saccharide structures in full detail, and at a temperature relevant to their structure and function, I note that the Eleventh Erwin Felix Lewy Bertaut Prize of the European Neutron Scattering Association (ENSA) and the European Crystallographic Association (ECA) was awarded to Dr Luka ´s ˇGajdos in 2022 for his PhD research at the Institut Laue-Langevin Grenoble as reported in Gajdos et al (2021Gajdos et al ( , 2022.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…protonation states of acidic residues in the carbohydratebinding site of LecB from the human pathogen P. aeruginosa (Gajdos et al, 2021(Gajdos et al, , 2022. The neutron crystal structures included apo and monosaccharide-bound forms; for an example of the fine details that can be seen in the nuclear density map, see Fig.…”
mentioning
confidence: 99%